2019
DOI: 10.1186/s41938-019-0139-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different cold storage periods of rearing host eggs on the performance of the parasitoid Trichogramma evanescens (Westwood) (Hymenoptera: Trichogrammatidae)

Abstract: Laboratory experiments were carried out to evaluate the acceptance of Trichogramma evanescens (Westwood) (Hymenoptera: Trichogrammatidae) to long and short cold storage periods of the host, the Angoumois grain moth, Sitotroga cerealella Olivier (Lepidoptera: Gelechiidae) eggs. The eggs were stored at 5°C for 5, 10, 15, 20, and 30 days, before exposing to the parasitoid. Fecundity, longevity, percentage of adult emergence, sex ratio, and general productivity (GP) were investigated. Storage period to 5 days show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Similarly, Gharbi (2014) reported that the longevity of T. oleae adults that emerged from stored pupae decreased significantly with increasing cold storage duration. Siam et al (2019), showed that the longevity of female T. evanescens decreased with prolonged Sitotroga cerealella (Olivier) (Lepidoptera: Gelechiidae) cold storage periods.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Gharbi (2014) reported that the longevity of T. oleae adults that emerged from stored pupae decreased significantly with increasing cold storage duration. Siam et al (2019), showed that the longevity of female T. evanescens decreased with prolonged Sitotroga cerealella (Olivier) (Lepidoptera: Gelechiidae) cold storage periods.…”
Section: Discussionmentioning
confidence: 99%
“…The number of parasitized eggs and the number of dead females during the first 7 days after their emergence were determined. Furthermore, the reduction in parasitization of T. bourarachae on E. kuehniella eggs was estimated as a function of cold storage procedure and cold storage period (Siam et al, 2019).…”
Section: Effect Of Cold Storage On T Bourarachaementioning
confidence: 99%
“…Long-term storage could supplement, or even replace, expensive continuous rearing practices currently being used in mass rearing facilities (Cagnotti et al, 2018). The ability to store insects could open new opportunities for producers of biological control agents to stockpile insects when levels of production are higher than levels of demand, and then deliver these insects quickly when demand increases (Siam et al, 2019). The two basic strategies for low-temperature storage of insects are (1) the cryopreservation of embryos at cryogenic temperatures, most often in liquid nitrogen at −196°C, and (2) long-term storage at temperatures below the threshold for development, which is typically applicable for insects in diapause but can also be used for insects induced into other types of deep states of dormancy (Leopold, 2007;Denlinger, 2008).…”
Section: Introductionmentioning
confidence: 99%